A study of the opinions and attitudes of Afrikaans speaking and English speaking teachers and student-teachers with regard to the teaching of scripture in primary and secondary schools : with special reference to the implementations of the scripture syllabuses of the Cape Department of Education - Broekmann, Daniel Matthew (Stellenbosch : Stellenbosch University, 2012)
Cover title: Scripture teaching in the Cape Province.